Thermal‐Oxidative Growth of Substoichiometric WO3–x Nanowires at Mild Conditions. Issue 10 (26th July 2020) - Spanu, Davide; Recchia, Sandro; Schmuki, Patrik; Altomare, Marco
Abstract : Herein, the growth of substoichiometric tungsten oxide (WO3– x ) nanowires (NWs) via thermal oxidation of W films (a few 10 to a few 100 nm thick) deposited by Ar‐plasma sputtering on fluorine‐doped tin oxide (FTO) substrates is reported. A thermal treatment at relatively low temperature (525–550 °C) in Ar at atmospheric pressure leads to the conversion of the W films into W suboxide (WO3– x ) NW arrays. Such NWs have a length of ≈500 nm and their diameter ranges from 10 to 40 nm depending on the duration of the annealing process. These growth conditions for the formation of WO3– x NWs are significantly milder and more straightforward than those reported in previous literature. This avoids high temperatures (e.g., above 600 °C), vacuum conditions, or the addition of catalysts. A thermal‐oxidative approach of these sputtered films is suitable to directly form WO3– x NWs on various surfaces, including conductive substrates to fabricate photoelectrodes or large‐scale supports, e.g., for smart windows. Abstract : A simple heat treatment at 525–550 °C under mild conditions (Ar atmosphere, ambient pressure, no catalysts) converts W films sputter‐coated on fluorine‐doped tin oxide (FTO) substrates into substoichiometric tungsten oxide (WO3– x ) single crystalline nanowires via a thermal‐oxidative growth mechanism. The approach is suitable to coat functional WO3– x nanowire layers on various surfaces.